Direito humano à memória da educação de adultos no Brasil autoritário: documentos legais e narrativas de ex participantes do MOBRAL (1967-1985) - Santos, Luciana Martins Teixeira dos (2015)
The privation period of freedoms and rights, established by the Civil Military Jab of 1964, contributed to the "forgetfulness" or "silent" of the memories. In this subjective and selective movement of the memory, that can "remember" or "forget", the human right to the memory of adults education in authoritarian Brazil is put in evidence. In this perspective, the present research of Right Humans Master/PPGDH/UFPB, of the Public Politics in Education in Right Humans Research Line, purposes to rebuild the education memory of the Brazilian Alphabetization Movement/MOBRAL, starting with the analyses of the legal and institutional documents that presents the ex-participants narratives of this movement. With this objective, the adopted methodological process is the bibliographic research, using the speech analyses to the collected memories and data interpretation. To found the study, we revolved some authors as LeGoff (2012), Halbwachs (2006), Bosi (1994), Pollak (1989), Silva (2003), Galzerani (2004), about the memory. About the interface between the Right Humans and the memory right, we used Barbosa (2007), Comparato (2007), Ferreira (2007, 2014), Sader (2007), Silva; Tavares (2010), Silveira (2007), Viola (2007, 2010), a Declaração Universal dos Direitos Humanos (1948), The National Plan of Education in Right Humans (2007), and others as source. About the MOBRAL, we were based on Paiva (1973); Freire (2011, 2013) e a Jannuzzi (1983) and institutional documents of the movement. And in the historical context of 1960’s beginning to 1985, was comprehended by the optic of Saviani (2008), Germano (1994), Romanelli (1983), Cunha e Góes (1985). With the MOBRAL memories reconstitution, we verified that the military regimen denied, to the adult students, the right of a critical and asker education, leaving to then an incomplete education or "by the half", resented of pedagogic knowledge and making, turned to the emancipation by the word. The right to a freedom education, inspired in Freire’s pedagogy of emancipation by the awareness/action has been denied to then. In this configuration, the MOBRAL represents a regression in the adults alphabetization history.